Prognostic factors in head and neck mucosal malignant melanoma. Issue 1 (February 2018) - Çomoğlu, Şenol; Polat, Beldan; Çelik, Mehmet; Şahin, Bayram; Enver, Necati; Keleş, Meryem Nesil; Sarı, Şule Öztürk
Abstract: Objective: Primary mucosal malignant melanoma of the head and neck (HN-PMMM) is an aggressive and uncommon neoplasm. Herein, we present a series of 33 patients and the results of treatment, and aimed to determine prognostic factors in HN-PMMM. Methods: Patients who were diagnosed as having HN-PMMM in our reference hospital, between 2005 and 2014 were evaluated. Thirty-three of these patients who had follow-up data were included. Surgical margin status was extracted from the original pathology reports. Archived materials were retrieved for the histopathologic findings: ulceration, necrosis, lymphovascular invasion, perineural invasion, pigmentation, and presence of an in situ component. Mitotic activity was evaluated using phosphohistone H3 (PHH3) immunohistochemical staining. Results: We found an association of PHH3 mitotic activity with overall survival in a univariate analysis and to our knowledge, this is the first report among the available case series of HN-PMMM to evaluate mitotic activity using immunohistochemical staining. We also investigated the relationship between multicentricity and locoregional recurrence, which the authors believe is also a first. Conclusion: PHH3 mitotic activity can be used a prognostic factor for head and neck mucosal malignant melanoma.